Closed-loop control of a dual-fuel engine working with different combustion modes using in-cylinder pressure feedback. (March 2020) - Guardiola, Carlos; Pla, Benjamín; Bares, Pau; Barbier, Alvin
This work presents a closed-loop combustion control concept using in-cylinder pressure as a feedback in a dual-fuel combustion engine. At low load, reactivity controlled compression ignition combustion was used while a diffusive dual-fuel combustion was performed at higher loads. The aim of the presented controller is to maintain the indicated mean effective pressure and the combustion phasing at a target value, and to keep the maximum pressure derivative under a limit to avoid engine damage in all the combustion modes by cyclically adapting the injection settings. Various tests were performed at steady-state conditions showing good abilities to fulfil the expected operating conditions but also to reject disturbances such as intake pressure or exhaust gas recirculation variations. Finally, the proposed control strategy was tested during a load transient resulting in a combustion switching-mode and the results exhibited the closed-loop potential for controlling such combustion concept.